Progress in non-viral localized delivery of siRNA therapeutics for pulmonary diseases - Jingjing Gao; Ziting Xia; Dilrasbonu Vohidova; John Joseph; James N. Luo; Nitin Joshi (Elsevier, 2023)
Emerging therapies based on localized delivery of siRNA to lungs have opened up exciting possibilities for treatment of different lung diseases. Localized delivery of siRNA to lungs has shown to result in severalfold higher lung accumulation than systemic route, while minimizing non-specific distribution in other organs. However, to date, only 2 clinical trials have explored localized delivery of siRNA for pulmonary diseases. Here we systematically reviewed recent advances in the field of pulmonary delivery of siRNA using non-viral approaches. We firstly introduce the routes of local administration and analyze the anatomical and physiological barriers towards effective local delivery of siRNA in lungs. We then discuss current progress in pulmonary delivery of siRNA for respiratory tract infections, chronic obstructive pulmonary diseases, acute lung injury, and lung cancer, list outstanding questions, and highlight directions for future research. We expect this review to provide a comprehensive understanding of current advances in pulmonary delivery of siRNA.